2021
DOI: 10.1158/0008-5472.can-21-1023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PIM Kinases in DLBCL Targets MYC Transcriptional Program and Augments the Efficacy of Anti-CD20 Antibodies

Abstract: The family of PIM serine/threonine kinases includes three highly conserved oncogenes, PIM1, PIM2, and PIM3, which regulate multiple prosurvival pathways and cooperate with other oncogenes such as MYC. Recent genomic CRISPR-Cas9 screens further highlighted oncogenic functions of PIMs in diffuse large B-cell lymphoma (DLBCL) cells, justifying the development of small-molecule PIM inhibitors and therapeutic targeting of PIM kinases in lymphomas. However, detailed consequences of PIM inhibition in DLBCL remain und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…synthetic lethality with MYC and synergy with anti-CD20 immunotherapy in preclinical models of MYCdriven TNBC and DLBCL, respectively [202,203].…”
Section: Synthetic Lethality: Exploiting Oncogenic Pathways For Their...mentioning
confidence: 99%
See 1 more Smart Citation
“…synthetic lethality with MYC and synergy with anti-CD20 immunotherapy in preclinical models of MYCdriven TNBC and DLBCL, respectively [202,203].…”
Section: Synthetic Lethality: Exploiting Oncogenic Pathways For Their...mentioning
confidence: 99%
“…Furthermore, the three PIM‐family kinases proved redundant for the cooperation with oncogenic MYC [ 200 ]. Several small molecule inhibitors of PIM kinases are currently in clinical development [ 191 , 201 ] and some of them showed synthetic lethality with MYC and synergy with anti‐CD20 immunotherapy in preclinical models of MYC‐driven TNBC and DLBCL, respectively [ 202 , 203 ].…”
Section: Myc and Therapy Resistancementioning
confidence: 99%
“…It has been reported that patients with DLBCL harboring MYD88 and/or CD79B mutations are more sensitive to BTKi ( 49 , 50 ). More recently, PIMi was reported to enhance the efficacy of CD20 antibodies by targeting MYC transcription ( 51 ). Inhibitors targeting epigenetic alterations have been widely studied, and the application of HDACi was considered to be a feasible solution for treating patients with KMT2D alterations ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed as previously described ( 20 , 21 ). Briefly, protein lysates were resolved by SDS-PAGE, transferred to PVDF membranes (Millipore) and immunoblotted with primary and appropriate HRP-labelled secondary antibodies (listed in Supplemental Table 1 ).…”
Section: Methodsmentioning
confidence: 99%